A Study of the Population Structure of Two Species of Non-human Primates in the Similipal Tiger Reserve, Mayurbhanj, Orissa, India - Swain, D.; Rout, S. D.; Behura, B. K. (Indian Forester, 2008)
Generally three species of non-human primates occur in the State of Orissa (India). Among these only two species of non-human primates occur in the forests of Similipal hills of Mayurbhanj District. A census for different species of wild mammals occurring in the Similipal Tiger Reserve was undertaken during May, 2004. The results of population structure of two species of non-human primates, viz. Semnopithecus entellus entellus and Macaca mulatta were furnished. The census was carried out for four consecutive days in the line transect method covering a total distance of 122 km. Of the 144 troops sighted consisting of 1,505 Hanuman langurs, the mean troop size worked out to 9.6 Â± 1.19. The highest and lowest density of Hanuman langur was 162.5 and 1.7 per km2 respectively. Similarly, out of 12 macaque troops sighted consisting of 138 individuals, the troops were made up of 4 to 25 individuals, with a mean of 11.5 Â± 1.82. The population density was 10-98.3 per km2, with a mean of 26.86.